2010
DOI: 10.1016/j.cmet.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyl Transferases and Demethylases; Can They Link Metabolism and Transcription?

Abstract: Summary Epigenetics is defined as heritable changes to the transcriptome that are independent on changes in the genome. The biochemical principles that govern epigenetic modifications are DNA methylation and posttranslational modifications of histones, amongst which acetylation/deacetylation and methylation/demethylation of lysine residues are the most widely studied. Such epigenetic changes are involved in many physiological and pathological processes. This essay will focus on the biology of histone methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
202
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(205 citation statements)
references
References 66 publications
0
202
0
3
Order By: Relevance
“…A growing body of evidence indicates the existence of an intimate link between the metabolic status and epigenetic regulation of cells (1,2). This is exemplified by the fact that a variety of small molecules involved in intercellular metabolism, including adenosine triphosphate, S-adenosylmethionine, nicotinamide adenine dinucleotide, flavin adenine dinucleotide, folate, acetyl coenzyme A, α-ketoglutarate and iron, are essential for the proper maintenance of the cellular epigenome.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates the existence of an intimate link between the metabolic status and epigenetic regulation of cells (1,2). This is exemplified by the fact that a variety of small molecules involved in intercellular metabolism, including adenosine triphosphate, S-adenosylmethionine, nicotinamide adenine dinucleotide, flavin adenine dinucleotide, folate, acetyl coenzyme A, α-ketoglutarate and iron, are essential for the proper maintenance of the cellular epigenome.…”
Section: Introductionmentioning
confidence: 99%
“…These functions are prominent features in proteins that mediate diverse protein-protein interactions and coordinate downstream events, including ubiquitination and histone methylation (45,46). Histone methylation is a reversible process catalyzed by specific and general histone methyltransferases and demethylases, which in turn rely on metabolic coenzymes and respond to changes in energy supply and metabolic status (47). The results of the present study demonstrated that the genome-wide changes in T2D were directly associated with the specific histone modifications in the process of histone methylation (48).…”
Section: Discussionmentioning
confidence: 99%
“…In animals the inhibition of endogenous HDAC-II has primarily caused cardiac myocyte hypertrophy and also induced modest cell death [22]. In contrast, inhibition of class I HDACs presented anti-hypertrophic effect [25]. Moreover, induced expression of class II HDAC in cardiomyocytes mimics hypertrophic growth in an Akt-dependent manner [26].…”
Section: Short Communicationmentioning
confidence: 99%